The mechanical behaviour of polyurethane foam: multiaxial and dynamic behaviour. (24th November 2009) - Peroni, Lorenzo; Avalle, Massimiliano; Peroni, Marco
In the work, polyurethane rigid foam for energy absorption in automotive applications has been considered. Polyurethane foams are very interesting in these applications because of the possibility to foam them in place filling the required volume space. The material behaviour has been studied by subjecting the foam to different stress state conditions, including uniaxial compression and tension, hydrostatic, and pure deviatoric. To achieve this objective, a series of experimental tests and of test specimens have been designed. The experimental devices have been constructed and the test results have been used to characterise the material. The results obtained from the different tests, allowed defining failure criteria for the foam, in terms of yield and post-yield behaviour. The influence of density (three different densities have been considered in the analysis), repeated loading, and strain-rate effects are also taken into account. For an effective interpretation of the results, the experimental data of all the tests have been interpolated by means of a particular material model: such model permits to describe in a simple way the foam behaviour in different stress conditions, making simpler, at the same time, the description of the global multiaxial behaviour.